Obesity as a Risk Factor for Work Accidents - Paixão, Mírian Patrícia Castro Pereira (2009)
Obesity as a Risk Factor for Work Accidents ABSTRACT: Obesity is a syndrome that affects large portion of the economically active population and this has been a concern for Public Health. Additonally, the labor market increasingly demands of professionals, so that they have little time to take care of their health. The accidents can be generated from the stress in which individuals live on the desktop or can be related to occupational diseases. Obesity is not part of the list of diseases related to work, but this may be responsible for various diseases that fall into this group. Some companies have become aware that obesity has led to absenteeism and suggests that prevention of this problem can be treated in the workplace in order to improve the worker life quality. Thus, the objective of this study through bibliographical research, was to relate work accident to changes in occupational health and characterize obesity as a risk factor for health and work accidents.